Application of Lean Methodology, 5S, VSM, and Kanban in a Peruvian Agro-export Company to Increase Economic Profitability - Rodríguez Mendoza, Miguel Ángel (2023)
In the supply chain and procurement operations of companies dealing with food or perishable products, numerous problems arise that lead to raw material loss due to process issues or inadequate communication with suppliers. This results in stockouts, causing economic and financial losses in companies’ operational results. Hence, the application of Lean methodology in purchasing and procurement operations within a medium-sized Peruvian agro-exporting company is proposed. Specifically, the use of 5S, Value Stream Mapping (VSM), and Kanban tools is recommended to solve or minimize the impact of direct causes leading to stockouts. Through the implementation of these tools and Lean methodology in a pilot program, significant improvements were achieved, including total savings of 26%, a 30% reduction in raw material inventory losses in warehouses, a 30% reduction in costs related to stockouts, 20% less waste, a 30% reduction in undelivered inputs, and a 25% reduction in purchase order processing times. These quantitative results demonstrate a positive impact from applying Lean methodology to purchasing and procurement operations.